The Effects of Prognostic Factors in Idiopathic Sudden Hearing Loss - Bulğurcu,Suphi (2018)
Abstract Introduction Sudden hearing loss is one of the otologic emergencies. The treatment of this disease is affected negatively by some prognostic factors. Objective In this study, the effects of early treatment initiation in patients with idiopathic sudden hearing loss and of prognostic factors in early treated patients were investigated. Methods Out of the 216 patients admitted between September 2007 and September 2015, 154 were identified as having idiopathic sudden hearing loss; they were followedup for a mean time of 7.4 months, and evaluated retrospectively. The effects of several parameters on the success of the treatment were statistically evaluated, such as the time the treatment was initiated, being of the female gender, the severity of the hearing loss, having descending type audiogram patterns, being older than 60 years old, and the co-presence of vertigo. Results Success rates were found to be significantly higher in idiopathic hearing loss patients that were admitted within the first week (p < 0.05) of the onset of the hearing loss. However, the outcomes were found to be similar when patients admitted within the first 3 days and 4-7 days after the occurrence of the hearing loss were compared (p > 0.05). Parameters such as female gender, severe hearing loss, descending type audiogram, being older than 60 years old, and co-presence of vertigo didn’t reveal statistically significant effects on the outcome (p >0.05). Conclusion The aforementioned prognostic factors, which are well-known in the literature, did not have significant effects when the idiopathic sudden hearing loss treatment was initiated within the first 7 days of the onset of the hearing loss.